Microstructures of Aspergillus spp. and their role in contaminating clinical solid wastes - Efaq Noman; Adel Al-Gheethi; Nik Norulaini Nik Ab. Rahman; Nagao Hideyuki; Balkis A Talip; Radin Mohamed; Mohd. Omar Ab. Kadir (Songklanakarin Journal of Science and Technology (SJST), 2020)
The aim of the current study was to describe the ultrastructure of Aspergillus spp. spores and conidiophores using Scanning Electron Microscope (SEM) and their role in contaminating of clinical solid wastes. Aspergillus spp. were described on, Czapek Yeast Extract Agar (CYA), Malt Extract Agar (MEA), Sabouraud Dextrose Agar (SDA), Czapek-Dox Agar (CZ) and Potato Dextrose Agar (PDA), while the ultrastructure of spores and conidiophores were observed using light Microscope and SEM. Fungal isolates were identified as A. caesiellus, A. terreus var. terreus; A. flavus, A. parasiticus, A. sydowii and A. Fumigatus with two new strains identified as Aspergillus sp. strain no. 145, Aspergillus sp. strain no. 311. SEM analysis for Aspergillus spp. conidiophores and spores were more useful in the taxonomy of fungi. Microstructures of the spores play important role in the contamination of clinical wastes, where the spiny fungal spores surface have high adherence for the solid wastes.